Protein Deficiency Attenuates the Effects of Alloxan on Insulin Secretion and Glucose Homeostasis in Rats - Prada, Francisco José A.; Luciano, Eliete [UNESP]; Carneiro, Everardo M.; Boschero, A. Carlos; Mello, Maria Alice R. [UNESP] (My University, 2001)
We have investigated the effect of alloxan on insulin secretion and glucose homeostasis in rats maintained on a 17% protein (normal protein, NP) or 6% protein (low protein, LP) diet from weaning (21 days old) to adulthood (90 days old). The incidence of alloxan diabetes was higher in the NP (3.5 times) than in the LP group. During an oral glucose tolerance test, the area under serum glucose curve was lower in LP (57%) than in NP rats while there were no differences between the two groups in the area under serum insulin curve. The serum glucose disappearance rate (Kitt) after exogenous insulin administration was higher in LP (50%) than in NP rats. In pancreatic islets isolated from rats not injected with alloxan, acute exposure to alloxan (0.05 mmol/L) reduced the glucose- or arginine-stimulated insulin secretion of NP islets by 78% and 56%, respectively, whereas for islets from LP rats, the reduction was 47% and 17% in the presence of glucose and arginine, respectively. Alloxan treatment reduced the glucose oxidation in islets from LP rats to a lesser extent than in NP islets (23% vs. 56%). In conclusion, alloxan was less effective in producing hyperglycemia in rats fed a low protein diet than in normal diet rats. This effect is attributable to an increased peripheral sensivity to insulin in addition to a better preservation of glucose oxidation and insulin secretion in islets from rats fed a low protein diet.